RECOMMENDATIONS FOR THE RECOVERY OF HIGHLY QUALIFIED FEMALE MARTIAL ARTISTS AFTER MANY YEARS OF TRAINING - Docent. Umarov Qahhorjon Abbasovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
It is presented to what extent the recommendations used in the rehabilitation of highly qualified female martial artists are used over many years of training.